Karen's roller skates ebook - Farina, Katy (Baby-Sitters Little Sister Graphix, 2020)
Another graphic novel in this fresh and fun series spin-off of The Baby-sitters Club, featuring Kristy's little stepsister! It's going to be a great weekend! Karen has new roller skates and is a very good skater. She's looking forward to trying some new tricks. But, oh no! Karen falls down and has to go to the hospital. Her wrist is broken! Karen is determined to get everyone she knows — plus someone famous — to sign her cast. It isn't going to be easy, but she won't give up until the job is done.